Between literature and science : Poe, Lem, and explorations in aesthetics, cognitive science, and literary knowledge - Swirski, Peter (McGill-Queen's University Press, 2000)
"Through close analysis of Eureka and The Purloined Letter, Peter Swirski evaluates Poe's epistemological theses in the light of contemporary philosophy of science and presents literary interpretation as a cooperative game played by the author and reader, thereby illuminating how we read fiction. The analysis of Poe's little-studied Eureka provides the basis for his discussion of Lem's critique of scientific reductionism and futurological forecasts. Drawing on his own interviews with Lem as well as analysis of his works, Swirski considers the author's scenarios involving computers capable of creative acts and discusses their socio-cultural implications. His analysis leads to bold arguments about the nature of literature and its relation to a broad range of other disciplines."--Jacket